Respon Bawang Putih Tunggal (Allium sativum L.) pada Aplikasi Lama Induksi Siplo dan Urine Kelinci - S Sugiarto; S Sunawan (Universitas Islam Malang, 2020)
Onions single (Allium sativum. L) relatively possess better qualities of nutritional content compared to bulbous garlic. Improving the quality and quantity of single garlic can be done through the improvement of cultivation. intensification of local potential systems techniques is a novel technology using electricity induction to improve physical chemical and biological properties in the soil. The electricity induction applied into the soil would increase ion and cation exchange in the ground. The purpose of this study was Improve the quality and quantity production of single garlic.The research used Randomized block design with two factors. Factors I: Time induction ( I0: 0 minutes, I1: 20, minutes I2: 40, minutes I3: 60 minutes). Factors II: Urine rabbits concentration ( U0: 0 ml /l, U1: 50 ml/l, U2: 100 ml/l, U3: 150 ml/l. The result showed a good impact of the application to the production. The application of 60 minutes electricity induction increased the production aroung 51.80 %. Keywords: single onions, induction siplo, urine